Analisis Tata Kelola Teknologi Informasi pada Universitas Adiwangsa Jambi Menggunakan Framework COBIT 2019 Domain EDM (Evaluate, Direct, Monitor) - Tiko Nurhaliza; Ni Luh Ayu Yaticha; M Rahul Fahlevi (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Information technology (IT) governance plays a strategic role in supporting the achievement of organizational goals, especially in higher education institutions. Adiwangsa University Jambi, as a private university, is required to manage IT effectively, efficiently, and in line with the institution's vision. This study aims to analyze the level of IT governance capabilities at Adiwangsa Jambi University using the COBIT 2019 framework with a focus on the EDM (Evaluate, Direct, Monitor) domain. The research method used is a descriptive quantitative method through data collection using questionnaires, interviews, and documentation studies. The results show that the level of IT governance capability in the EDM domain is at level 2 (Managed Process), indicating that the IT governance process is running but still needs improvement in several aspects, especially in monitoring and controlling IT performance. This study is expected to provide recommendations for Adiwangsa University Jambi in improving IT governance in a sustainable manner.